2017
DOI: 10.1111/1462-2920.13825
|View full text |Cite
|
Sign up to set email alerts
|

Cascading influence of inorganic nitrogen sources on DOM production, composition, lability and microbial community structure in the open ocean

Abstract: This work demonstrates that inorganic nitrogen sources can differentially influence the composition and lability of microbially-produced dissolved organic matter (DOM) with subsequent effects on heterotrophic community metabolism and microbial phylogenetic structure over weekly timescales in the open ocean. SummaryNitrogen frequently limits oceanic photosynthesis and the availability of inorganic nitrogen sources in the surface oceans is shifting with global change. We evaluated the potential for abrupt increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 98 publications
(116 reference statements)
1
18
0
Order By: Relevance
“…Arandia‐Gorostidi et al, 2017 for heterotrophic bacteria), we have found strongly coherent seasonal patterns in agreement with Burnside and colleagues (). The subtle equilibrium between bottom‐up and top‐down controls making temperature a relevant factor is intimately linked to inorganic nutrient concentrations, and likely also organic forms through cascading effects (Goldberg et al ., ). We concur with Cross and colleagues () that the future reshaping of microbial plankton communities will likely be determined by nutrient availability.…”
Section: Discussionmentioning
confidence: 97%
“…Arandia‐Gorostidi et al, 2017 for heterotrophic bacteria), we have found strongly coherent seasonal patterns in agreement with Burnside and colleagues (). The subtle equilibrium between bottom‐up and top‐down controls making temperature a relevant factor is intimately linked to inorganic nutrient concentrations, and likely also organic forms through cascading effects (Goldberg et al ., ). We concur with Cross and colleagues () that the future reshaping of microbial plankton communities will likely be determined by nutrient availability.…”
Section: Discussionmentioning
confidence: 97%
“…Two mock communities containing 22 taxonomically distinct clones (Supporting Information Table S2) were constructed from cloned full‐length bacterial and archaeal 16S rRNA gene amplicons from 4 surface samples, covering multiple seasons and diverse physicochemical conditions, and 1 subeuphotic zone (150 m) sample, all from the time‐series study (see Supporting Information Experimental Procedures). Taxonomies were assigned both with mothur (v1.39; Schloss et al ., ) using a non‐redundant subset of the SILVA SSU Ref16S alignment database (v115; Quast et al ., ) custom curated as in Goldberg and colleagues () and with the SILVA Incremental Aligner V1.2.11 (Pruesse et al ., ) using SILVA v132. Because bacterial and archaeal taxonomies remain in flux, we have used the SILVA v115 taxonomy throughout for consistency, but clone identities based on both v115 and v132 are specified in Supporting Information Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Although nitrification does not directly influence the system inventory of N, it alters the presence of N from its most reduced form, ammonia (NH 3 ), to its most oxidized form, nitrate (NO − 3 ) (Ward, 2005). This may affect not only the productivity of the system but also the composition of the phytoplankton and the microbial community since different groups are known to have preferences for nitrate or ammonium respectively Glibert et al, 2016;Goldberg et al, 2017). Further, nitrate is important as substrate for denitrification, and nitrification may therefore indirectly facilitate N loss .…”
Section: Introductionmentioning
confidence: 99%